Early postoperative respiratory acidosis after large intravascular volume infusion of lactated ringer's solution during major spine surgery - (:unkn) unknown (My University, 2002)
In this study, we compared the effects of large intravascular volume infusion of 0.9% saline (NS) or lactated Ringer's (LR) solution on electrolytes and acid base balance during major spine surgery and evaluated the postoperative effects. Thirty patients aged 18-70 yr were included in the study. General anesthesia was induced with 5 mg/kg thiopental and 0.1 mg/kg vecuronium IV. Anesthesia was maintained with oxygen in 70% nitrous oxide and 1.5%-2% sevoflurane. In Group I, the NS solution, and in Group II, the LR solution were infused 20 mL. kg(-1). h(-1) during the operation and 2.5 mL. kg(-1). h(-1), postoperatively. Electrolytes (Na+, K+, Cl-) and arterial blood gases were measured preoperatively, every hour intraoperatively and at the 1st, 2nd, 4th, 6th, and 12th hours postoperatively. In the NS group, pHa, HCO3 and base excess decreased, and Cl- values increased significantly at the 2nd hour and Na+ values increased at the 4th hour intraoperatively (P < 0.001). The values returned to normal ranges at the 12th hour postoperatively. In the LR group, blood gas analysis and electrolyte values did not show any significant difference intraoperatively, but the increase in PaCO2 and the decrease in pHa and serum Na+ was significant at the 1st hour postoperatively. Although intraoperative 20 mL. kg(-1). h(-1) LR infusion does not cause hyperchloremic metabolic acidosis as does NS infusion, it leads to postoperative respiratory acidosis and mild hyponatremia. IMPLICATIONS: The infusion of large-volume lactated Ringer's solution does not cause hyperchloremic metabolic acidosis as does 0.9% saline during major surgery, but leads to postoperative mild hyponatremia and respiratory acidosis.
Keywords: Adult; Female; Humans; Middle Aged; Postoperative Complications; Aged; Male; Orthopedic Procedures; Hemodynamics; Infusions, Intravenous; Monitoring, Intraoperative; Sodium Chloride; Spine; Carbon Dioxide; Isotonic Solutions; Ringer's Lactate; Anesthesia; Bicarbonates; Acid-Base Equilibrium; Acidosis, Respiratory; Blood Volume